Nurses Attitude to Patient Fall Prevention: The Influence of Nursing Training on Attitude Change - Pernavaitė, Ieva; Raškelienė, Vilma (Slauga. Mokslas ir praktika, 2022)
Problem. For patients, falls can cause physical injury, psychological consequences, prolong hospital stays, and increase the cost of treatment. Therefore, in order to ensure the best possible prevention of patient falls, it is important to update the nurse‘s knowledge and form a positive attitude towards the prevention of patient falls. Aim. To compare the change in nurses‘ attitudes about patient fall prevention before and after the delivery of the training material. Methods. Quantitative research and an anonymous questionnaire were conducted. The study participants were general practice nurses from the Lithuanian University of Health Sciences hospital Kaunas Clinics. The survey was conducted twice: before and after the delivery of the training material. Results and conclusions. Both before and after the educational material, nurses rated discussion of the causes of falls in a meeting as the most effective and leadership as the least effective fall prevention tool in teamwork. Also, both before and after the educational material, nurses rated the appropriate ward environment as the most effective fall prevention tool, but the least agreed that fall risk assessment tools were a better tool than nurses’ personal fall risk assessment. However, after the educational material, the nurses’ attitude became more positive both regarding the organization of falls prevention in the team and the importance of fall prevention measures. It was also found that the attitude of nurses with non-university higher education or university higher education towards the prevention of patient falls was more positive compared to nurses with higher education.